2015
DOI: 10.1589/jpts.27.705
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between foot posture measurements and force platform parameters during two balance tasks in older and younger subjects

Abstract: [Purpose] The aim of this study was to compare age-related differences in balance and anthropometric posture measurements of the foot and to determine any relationship between them. [Subjects and Methods] Sixty-eight older and 42 younger adults participated in this study. Foot posture was tested for four domains: 1) hallux flexion and extension range of motion using a goniometer, 2) navicular height and 3) length of the foot using a pachymeter, and 4) footprint (width of forefoot, arch index and hallux valgus)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 38 publications
2
18
0
4
Order By: Relevance
“…However, Carvalho et al 12 demonstrated the relation of low mobility of the hallux with plantar pressure increase in older adults when compared to young adults. The fact this joint has not been investigated by this study justifies the absence of the relation between the ROM of LL with plantar pressure increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Carvalho et al 12 demonstrated the relation of low mobility of the hallux with plantar pressure increase in older adults when compared to young adults. The fact this joint has not been investigated by this study justifies the absence of the relation between the ROM of LL with plantar pressure increase.…”
Section: Discussionmentioning
confidence: 99%
“…Such alterations affect the musculoskeletal system, accompanied by a loss of muscle mass, decrease of strength and ROM of lower limbs (LL), of endurance [6][7][8] and alterations in bone structure, such as alterations in the feet, influencing plantar pressure distribution, affecting the somatosensory information and therefore, balance [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…If the shift in the center of gravity changes minimally, this relation is changed so that one foot has to carry more total load. Therefore, pressure plates are a suitable instrument for measuring balance and postural stability [5][6][7][8][9][10][11]. When the body weight is transferred, the pressure is distributed most strongly in the hindfoot, then decreasingly in the midfoot and forefoot.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, this study found that HVA can help increase the path of the COP shift rather than plantar pressure, according to linear regression analysis. Carvalho et al [27] asserted that HV could affect sway during shifts of the COP to varying degrees, depending on the forefoot width and foot arch. Wen et al [13] reported that contact time extends as motions increase loading on the lateral and medial rear foot regions.…”
Section: Discussionmentioning
confidence: 99%